Relationships among Physicochemical, Microbiological, and Parasitological Parameters, Ecotoxicity, and Biochemical Methane Potential of Pig Slurry - Beily, María Eugenia (2023)
Background: Pig slurry can negatively impact on the environmental, animal, and human health. Knowing the relationship between the organic and inorganic loads, pathogens, and toxicity allows identifying the main parameters to be removed or treated before final disposal. The aim of this study was to evaluate the relationships between the physicochemical properties, microbiological, and parasitological content, ecotoxicological effects, and biochemical methane potential (BMP) of pig slurries. Methods: Ten pig slurry samples at two production stages were characterized and a BMP test at two substrate/inoculum (S/I) ratios was conducted to compare the methane yields. Results: We found high content of Cu, Zn, quaternary ammonium, pathogenic microorganisms (E. coli and Salmonella), and parasites (Trichuris and Trichostrongylus). Toxicity on lettuce, radish, and Daphnia was observed with a slurry concentration greater than 1.35%. Positive correlations were found between toxicity on Daphnia and chemical oxygen demand (COD), sulfate, Zn, and Cu, as well as between phytotoxicity and COD, NH4, Na, K, and conductivity. The lowest S/I ratio showed 13% more methane yield. It was associated with high removals of COD and volatile fatty acids. Conclusions: We recommend using a low S/I ratio to treat pig slurry as it improves the efficiency of the anaerobic process.